Aerodynamic impact of cycling postures on drafting in single paceline configurations - van Druenen, T.; Blocken, B. (Computers & Fluids, 2023)
This paper presents finite-volume-based scale-adaptive simulations of single paceline configurations up to eight cyclists for three different postures. In cycling, drag reduction by drafting in pacelines is a key strategy to limit energy expenditure. The drag reductions of individual cyclists and of the paceline as a whole are determined by several factors, including cycling posture. To the best of our knowledge, a systematic study on the effect of cyclist posture on the drag in single pacelines has not yet been published in the scientific literature. In this study, drag reduction and flow field data were computed while validation was performed by wind tunnel measurements. The three investigated postures concern a road race dropped posture with either a large or small sagittal torso angle and a time trial posture. For the considered pacelines in which all cyclists have the same posture, the drag of a cyclist could be reduced by changing either the posture, or the position, or both. Changing posture can yield a maximum drag reduction of about 15% for the leading cyclist. The position in the paceline with minimum drag was the one but last, independent of the investigated cycling postures. For the pacelines containing eight cyclists, maximum drag reductions up to 63% were found. The largest drag reduction was 68%, obtained by riding in penultimate position in an eight cyclist paceline in dropped position with a small sagittal torso angle.